Global Religious Diversity Values in the Study of International Relations Courses and Their Contributions in Character Education - Shofia Nurun Alanur S; Hasdin; Jamaludin (Journal of Islamic Education Research, 2022)
One of the educational missions that continue to be echoed is character education. Although the development of science and technology is advanced and evolving, to face the metaverse era, characters must continue to be directed, shaped and guided, especially among students as a younger generation. One of the values that must be strengthened is the value of religious and global diversity, from the profile of Pancasila students. Global diversity means being open-minded in interacting with other cultures, maintaining self-identity, and believing that such attitudes are part of the fear of God Almighty. This research aims to examine and describe these values in international relations courses. Data is collected through interview methods and literature studies of the subject matter. Data analysis uses reduction techniques, conclusions and data presentation. The results showed that in international relations courses, the value of global diversity is highly integrated. Discussion of international relations, international cooperation, international treaties, the international community and issues in international relations. The value of global character-diversity is needed in international associations. Strengthening religious values in the self so as not to be easily affected from the international negative environment. Understanding other cultures that are equipped with faith, solidarity and love for their own culture, giving birth to a generation that is able to interact with the world, take positive knowledge and lessons, and implement the progress of the country. This condition contributes to the efforts of character education and the formation of global citizens who uphold the value of faith in god.